Stability Analysis for Fractional-Order Linear Singular Delay Differential Systems - Hai Zhang; Daiyong Wu; Jinde Cao; Hui Zhang (Discrete Dynamics in Nature and Society)
We investigate the delay-independently asymptotic stability of fractional-order linear singular delay differential systems. Based on the algebraic approach, the sufficient conditions are presented to ensure the asymptotic stability for any delay parameter. By applying the stability criteria, one can avoid solving the roots of transcendental equations. An example is also provided to illustrate the effectiveness and applicability of the theoretical results.